Early detection of Fetal Acrania on first-trimester sonography: a case report - I Nyoman Hariyasa Sanjaya; Cokorda Istri Mirayani Pemayun; Ni Komang Anik Pirgantari; Made Diah Vendita Sakuntari; Ni Wayan Dewi Purwanti; NI Putu Nining Gianni; Ni Luh Made Diah Mas Cahyani Putri; Ni Luh Md Dwi Laxmi Satriani; Firsta Sesarina Mintariani; Ni Luh Putu Yulia Padmawati; Anak Agung Wahyu Putri Agustini (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2021)
Introduction. Fetal Acrania is a rare fetal malformation characterized by the complete or partial absence of a skull covering the fetal brain. In the absence of a hard covering of the soft brain tissue, Acrania is known as a universally lethal malformation. Here we present a Fetal Acrania case detected by sonographic examination at our Center. Case Description. A 36 years old female was referred to the obstetric department to undergo an in-depth sonographic evaluation as a previous examination reveals a potential congenital fetal anomaly. Our sonographic evaluation revealed a singleton, live fetus, 12 weeks gestational age in cephalic presentation and longitudinal lie. One obvious malformation was a well-formed fetal brain without the surrounding cranium (Acrania). The absence of cranium was the main and only malformation. The absence of cranium was evident as the fetal brain was easily compressed on probe pressure, and the brain appeared like floating in the amniotic fluid over the base of the skull. Therapeutic abortion was carried out. The termination was conducted by administering four tablets of 200 mcg misoprostol sublingually and repeated 24 hours later. No adverse reaction or complication on termination. The aborted fetal examination confirmed the lack of fetal cranium. Conclusion. Although seemingly obvious, the first-trimester diagnosis of fetal Acrania must be made with caution as the fetal cranium is not fully calcified before 10- 11 weeks. As Acrania is a universally lethal malformation, therapeutic abortion is indicated.